Surgical Treatment of Idiopathic Enlargement of the Right Atrium. (20th September 2018) - Surace, Francesca Chiara; Iezzi, Federica; Colaneri, Massimo; Pozzi, Marco
Abstract : Idiopathic enlargement of the right atrium (IERA) is a very rare abnormality. Approximately one-half (48%) of the patients with a congenital enlargement of the right atrium have no symptoms. When they occur, symptoms include shortness of breath (28% of cases), palpitations (17%), arrhythmias (12%), and in rare cases, right heart failure and extreme tiredness. We report one such case of a young man with a disproportionally enlarged right atrium. The basal transthoracic echocardiogram demonstrated a huge right atrium with a thick smoke pattern and mild tricuspid regurgitation in the absence of congenital heart disease. Magnetic resonance imaging confirmed the right atriomegaly, with initial compression of the right ventricle, and excluded congenital heart defects or absence of pericardium. The patient underwent surgical resection of the right atrial wall and the atriotomy was closed, leaving an atrial chamber of normal consistency and size. The resected atrium had normal and homogeneous wall thickness without significant fibrosis which confirmed the diagnosis of an idiopathic enlargement of the right atrium.